Peranan Pembiyaan Murabahah dalam Pengembangan Usaha Pada PT Bank Muamalat - Rudi Abdullah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
The purpose of this study to determine how the role of murabahah financing in developing the business at PT. Bank Muamalat Branch Baubau Assistant. The population in this study is 268 number of customers in Murabahah Financing At PT. Bank Muamalat Branch Baubau Assistant. The method used is descriptive method of collecting data obtained and then interpret and analyze it so as to provide information that can be used to solve problems encountered. The data used are primary data and secondary data. This research concludes that the role of murabahah financing product in BMI has applied financing principle in accordance with Fatma Dewan Syariah Nasional. 04 / DSN MUI / IV / 2000. About Murabahah in every financing transaction by paying attention to contract, sale price, financing requirement, term of financing, way of mortgage financing, and also pay attention to murabahah financing role at bank muamalat. The authors suggest that PDD BIM should improve professionally delivered, in terms of products, services, and implementation in accordance with sharia principles.